Killing in war - McMahan, Jeff. (Oxford : Clarendon, 2009)
Jeff McMahan urges us to reject the view, dominant throughout history, that mere participation in an unjust war is not wrong. He argues powerfully that combatants who fight for an unjust cause are acting wrongly and are themselves morally responsible for their actions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: War -- Moral and ethical aspects; Combat -- Moral and ethical aspects; Military ethics; Conscientious objection; Responsibility